PEMBERDAYAAN KADER POSYANDU UNTUK MENURUNKAN ANGKA KEJADIAN STUNTING - Widhidewi, N.W.; Paramasatiari, A.A.A.L.; Apsari, P.I.B.; Suriati, L.; Sutisna, P. (Buletin Udayana Mengabdi; Vol 23 No 2 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i02.p12, 2023)
Stunting is a condition of failure to thrive in children below 5 years old because of chronic nutritional depletion, which resulted in the posture that too short for the age. To date, stunting still become one of the important health problems in Indonesia. Although the data from Riskesdas have shown that there was decrease in the stunting rate from 37.2% in 2013 to 30,8% in 2018, but prevention measures still need to be socialized. In Bali, stunting prevalence in 2018 was 21.9%. In the scope of Puskesmas Sukawati II, there is 49 cases of stunting (2.23%). Ten cadre of posyandu in Banjar Kederi, Silakarang and Samu, Singapadu Kaler Village, Gianyar Regency were included in this community service. The aim of this community service was to increase the posyandu cadre`s knowledge about stunting prevention, including the techniques of processing foods to maintain its nutritional content. We performed a workshop with power point slides and videos. Based on pre-test and post-test marks, there was an 21% increase in participant`s knowledge. We also gave endowments in the form portable wastafels and thermoguns. We hope that the posyandu cadre can educate pregnant woman and parents to prevent stunting. Keywords: stunting, cadre, posyandu, community service